Exploring AI Adoption for Digital Legal Compliance in MSMEs: A Qualitative Study from Karanganyar Regency, Indonesia - Marina Ramadhani; Arseto Endro Supriyanto; Yayu Sri Rahayu (Journal of Management Studies and Development, 2026)
This study aims to explore the challenges and opportunities of applying Artificial Intelligence (AI) in supporting digital legal compliance among MSMEs in Karanganyar Regency, Indonesia. Using a qualitative approach based on in-depth interviews with MSME actors, technology practitioners, and legal experts, the research findings grouped the main issues into eight themes: low understanding of digital regulations, limited resources, perception of legal sanctions, regulatory fragmentation, the potential of AI for real-time monitoring, technical implementation challenges, consumer trust and privacy issues, and the role of local government in policy intervention. The analysis shows that although AI offers potential solutions to improve compliance, its implementation is still hampered by technical, cultural, and institutional factors. This study concludes that the successful application of AI to SMEs' digital legal compliance is highly dependent on institutional support and affirmative local policies.